Jonathan Ly: capstone - Ly, Jonathan, artist (Colorado State University. Libraries, 2020)
The artist's statement: The scope of my art ranges from brand design, digital art, to design communication. My greatest growth as an artist during this time, however, was not learning these complex programs but rather the foundation of graphic design. My studies have led me to better conceptualize my initial ideas and exploring them to get to the final project. Without this foundation, my art would not be able to communicate its themes and statements through interesting visuals as it does now. As a graphic design artist, I see myself as someone who works to create quality and innovative designs for my client’s wants and needs. My job as an artist provides me unique opportunities to create art based on my patron's needs and imaginations. I take this on as a challenge, like a puzzle, trying to find a solution that fulfills all requirements that have been laid out to me. One of my responsibility as a graphic design artist is to have the highest quality communication with the client to get the best possible end product. My process starts by offering multiple pencil sketches and ideas to provide as many possible routes as possible. This gives the patron many choices and iterations to explore a building block for the entire project. Using these sketches and exchanges as a foundation of where the project is going, I go through multiple rounds of prototyping through various adobe products and programs to better help translate and visualize my client's ideas. Only after these various rounds of prototyping will I begin my final designs with the client’s blessing. It is important to be clear and concise with the client as graphic designer, since the quality of the project depends on it. Having a complete understanding of every part of the project is key because it ensures that the client is happy in every possible and that the integrity of my art remains at the highest quality possible. From the simplest designs like a simple sticker set, to even a complex logo rebranding project it is important to create the quality content that speaks for the client in the way they see fit.
Colorado State University Art and Art History Department capstone project.
Capstone contains the artist's statement, a list of works, and images of works.
Keywords: graphic design